2012
DOI: 10.1603/ec11335
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cytochrome P450 Genes, CYP6EB1 and CYP6EC1, Are Over-Expressed in Acrinathrin-Resistant <I>Frankliniella occidentalis</I> (Thysanoptera: Thripidae)

Abstract: Control of Frankliniella occidentalis (Pergande) is a serious problem for agriculture all over the world because of the limited range of insecticides that are available. Insecticide resistance in F. occidentalis has been reported for all major insecticide groups. Our previous studies showed that cytochrome P450-mediated detoxification is a major mechanism responsible for insecticide resistance in this pest. Degenerate polymerase chain reaction was used to identify P450 genes that might be involved in acrinathr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 63 publications
0
17
0
1
Order By: Relevance
“…O-Methylation plays key roles in plant defense following pathogen attack [32]. Additionally, the interaction network suggests the possible involvement of Cytochrome P450 (CYP) genes (CYP72A7 and CYP71A26) in resistance, previously reported in several studies [33,34]. In the susceptible genotype, CYP83B1 gene required for the synthesis of indole glucosinolates, was down-regulated during infestation which is not consistent with previous reports in a number of researches [27,35].…”
Section: Secondary Metabolismmentioning
confidence: 61%
“…O-Methylation plays key roles in plant defense following pathogen attack [32]. Additionally, the interaction network suggests the possible involvement of Cytochrome P450 (CYP) genes (CYP72A7 and CYP71A26) in resistance, previously reported in several studies [33,34]. In the susceptible genotype, CYP83B1 gene required for the synthesis of indole glucosinolates, was down-regulated during infestation which is not consistent with previous reports in a number of researches [27,35].…”
Section: Secondary Metabolismmentioning
confidence: 61%
“…Cytochrome P450s (CYPs) are a large, ancient superfamily of enzymes identified in all domains of life and are involved in the metabolism of multiple substrates with prominent roles in hormone synthesis and breakdown, development, and detoxification [82, 83]. In agricultural systems, F. occidentalis has shown a propensity for developing resistance to insecticides commonly utilized to manage this species, and P450s have been specifically implicated in the detoxification of insecticides by F. occidentalis [84, 85]. Within the F. occidentalis genome, we identified and classified (CYP nomenclature) a relatively large number of P450s (130 models compiled into 89 complete genes, 23 partial sequences) of 24 different CYP families ( Additional file 2: Table S13 ), where, like in other insects, the CYP4 and CYP6 gene families are overrepresented – these families include members frequently associated with the breakdown of toxic plant products and insecticides [84].…”
Section: Plant Feedingmentioning
confidence: 99%
“…In agricultural systems, F. occidentalis has shown a propensity for developing resistance to insecticides commonly utilized to manage this species, and P450s have been specifically implicated in the detoxification of insecticides by F. occidentalis [84, 85]. Within the F. occidentalis genome, we identified and classified (CYP nomenclature) a relatively large number of P450s (130 models compiled into 89 complete genes, 23 partial sequences) of 24 different CYP families ( Additional file 2: Table S13 ), where, like in other insects, the CYP4 and CYP6 gene families are overrepresented – these families include members frequently associated with the breakdown of toxic plant products and insecticides [84]. Phylogenetic analysis revealed expansions in clan CYP 3 (CYP6 gene family) and clan CYP4 within F. occidentalis ( Additional file 1: Section 7.1, Fig S7.1 ).…”
Section: Plant Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CYP1A is one of the CYPs involved in aryl hydrocarbon receptor-mediated oxidation of xenobiotics, such as benzo( a )pyrene (B a P) (Nakata et al, 2006); the expression of CYP1A mRNA, and the protein, has been used as a sensitive biomarker for B a P (Van der Oost et al, 2003). The CYP6 families in terrestrial invertebrates have frequently been shown to play a role in the detoxification of xenobiotics and metabolic resistance to insecticides (Liu et al, 2010; Poupardin et al, 2010; Cifuentes et al, 2012; Musasia et al, 2013; Edi et al, 2014; Sun et al, 2014). However, the response of CYP6 in aquatic invertebrates to environmental pollutants has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%